Setting up a Decision Support System with Decision Tables - Schwarz, V.; Hohenberger, P.; Köhler, C. O.; Schlag, P. (Methods of Information in Medicine, 1989)
The aim of our study was to develop a decision support system using a conventional method which can be used as a shell for different applications. So it was necessary to find a method which allows separation of decision principles and decision algorithms. In addition, documentation of the patient records should be simplified. This could be attained by using the decision table technique and the programming language MUMPS.The general system developed was applied to the therapy decision for patients with liver metastases. The application system was clinically evaluated in a randomized group of patients. In 84% of the study group the therapy proposal of the system concurred with the therapy actually applied.Representation of knowledge in the form of tables is easily understandable by physicians. Since decision tables can be seen as a medium of communication between physician and system manager, knowledge acquisition is simplified.
Keywords: Decision Support; Decision Tables; Evaluation of Applications; Liver Metastases; MUMPS